2007
DOI: 10.1002/icd.450
|View full text |Cite
|
Sign up to set email alerts
|

Children's understanding of modesty in front of peer and adult audiences

Abstract: Previous research has suggested that the understanding of modesty—downplaying one's achievements to evoke a positive social evaluation—develops in the primary school years. However, very little is known about how children's understanding of modesty is associated with social contextual factors, such as audience type. A sample of 92 children aged 8–11 years responded to hypothetical vignettes where the protagonist responded either modestly or immodestly to praise. The findings supported earlier indications of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
101
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(114 citation statements)
references
References 16 publications
11
101
2
Order By: Relevance
“…Lee et al (2001) asked for moral judgments about characters lying about good deeds (white lies). Meanwhile, Banerjee presented statements that minimized the achievements of the characters as self-presentational tactics (Banerjee 2000(Banerjee , 2002Banerjee & Yuill, 1999, Watling & Banerjee, 2007. Both methods revealed that the period between six and ten years of age is when complex interpersonal reasoning developed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al (2001) asked for moral judgments about characters lying about good deeds (white lies). Meanwhile, Banerjee presented statements that minimized the achievements of the characters as self-presentational tactics (Banerjee 2000(Banerjee , 2002Banerjee & Yuill, 1999, Watling & Banerjee, 2007. Both methods revealed that the period between six and ten years of age is when complex interpersonal reasoning developed.…”
mentioning
confidence: 99%
“…This reasoning is linked to the complex theory of mind and socio-emotional and moral competencies. All of these are, in turn, related to the appropriate use of emotion display rules and self-presentational tactics linking affective and cognitive social knowledge (Watling & Banerjee, 2007). Self-presentation rules require individuals to know and manage the information displayed about themselves in order to create an acceptable public image.…”
mentioning
confidence: 99%
“…For example, they expect people to act more modestly around peers than teachers (Watling & Banerjee, 2007). Moreover, school-age children and adolescents expect people to disclose academic performance with peers who performed at a similar level to their own (Heyman et al, 2008;Zhang et al, 2014).…”
mentioning
confidence: 99%
“…Parker and Gottman's (1989) careful formulation of the development of peer relations in childhood suggests that children from around 8 years onwards become increasingly concerned about gaining social acceptance into peer groups, and it seems likely that these concerns make social evaluation highly salient for children at this time. In correspondence with this, researchers have reported developmental progress between 6 and 11 years of age in children's use and understanding of various impression management tactics (Bennett & Yeeles, 1990a;Bennett & Yeeles, 1990b;Watling & Banerjee, 2007a;Watling & Banerjee, 2007b). Moreover, children from around 8 years of age become increasingly able to recognize that self-presentational behavior may be adjusted to suit the distinctive preferences of different audiences (Banerjee, 2002b).…”
Section: Self-presentational Features In Childhood Social Anxietymentioning
confidence: 93%
“…However, some evidence has been found for the use or understanding by elementary school children of ingratiation and self-promotion (e.g., Aloise-Young, 1993;Bennett and Yeeles, 1990;Watling & Banerjee, 2007a), modesty (e.g., Banerjee, 2000;Watling & Banerjee, 2007b), disclaimers (e.g., Bennett, 1990), and excuses (e.g., Juvonen, 1996;Ohbuchi & Sato, 1994). We believe that individual differences in childhood social anxiety may be associated with variability in the tendency to use self-presentational tactics.…”
Section: Self-presentational Tacticsmentioning
confidence: 99%